Influence of subcritical water pretreatment temperature on pineapple waste biogas efficiency: experimental and kinetic study - Aili Hamzah, Adila Fazliyana; Hamzah, Muhammad Hazwan; Che Man, Hasfalina; Jamali, Nur Syakina; Siajam, Shamsul Izhar (College of Engineering, Mustansyriah University, 2024)
Anaerobic digestion of pineapple waste appears to be an effective method for non-renewable energy substitution through biogas production. The potential power generation from the exploitation of pineapple waste as fuel is estimated to be roughly 20.8 MW. Nevertheless, the intricate composition of pineapple waste, characterized by the complex arrangement of its structure, poses a significant challenge in attaining a substantial amount of biogas production. This study pretreated pineapple waste with subcritical water to increase biogas production. Two temperature settings (120⁰C and 200⁰C) were used for pretreatment. Combined pre-treatment at low temperatures and short time (120⁰C, 5 minutes, 10 water to solid ratio) resulted in 31.6% higher biogas production than untreated. However, pretreatment at high temperatures and longer reaction time (200⁰C,25 min) reduced the biogas production by 9% as compared to untreated. Using the Modified Gompertz kinetic model, pretreatment improved the lag phase and increased biogas production to 14.41 mL/day. The lignocellulosic composition of pre-treated pineapple waste decreased, while process parameters such as total ammonia nitrogen removal and pH improved after the pretreatment. Subcritical water pretreatment, particularly when conducted at high temperatures, did not yield any enhancements in the anaerobic digestion of pineapple waste. As a result, it is not advisable to employ this method for these purposes.